Dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) from river, lagoon, and open ocean sites along the Alaska Beaufort Sea coast, 2018-ongoing - Beaufort Lagoon Ecosystems LTER, Core Program (Arctic Data Center, 2019)
Multiple water types (river, lagoon, ocean) from the North Slope of Alaska and nearshore Beaufort Sea were sampled seasonally to investigate biogeochemical linkages between terrestrial, lagoon, and open ocean ecosystems. Water samples were collected in April, June, July, and August and analyzed for dissolved organic carbon and total dissolved nitrogen content.